Promotion du figuier de Barbarie dans les systèmes agrosylvopastoraux à faible pluviométrie d’Asie du Sud et du MENA - Louhaichi, Mounir; Hassan, Sawsan (Agropolis International, 2022)
A chapter in Agroecology Transformation for Sustainable Food Systems: Insight on FRANCE-CGIAR Research, The publication reflects the enormous opportunity ahead to enhance the complementarity of crop and livestock farming through prompting different technologies. This chapter is highlighting the role of drought resilient multi-purpose crops in low rainfall agrosylvopastoral systems in MENA and South Asia to respond to the challenges facing our food, land, and water systems